RNA- binding protein Stau2 is important for spindle integrity and meiosis progression in mouse oocytes. Issue 19 (1st October 2016) - Cao, Yan; Du, Juan; Chen, Dandan; Wang, Qian; Zhang, Nana; Liu, Xiaoyun; Liu, Xiaoyu; Weng, Jing; Liang, Yuanjing; Ma, Wei
ABSTRACT: Staufen2 (Stau2) is a double-stranded RNA-binding protein involved in cell fate decision by regulating mRNA transport, mRNA stability, translation, and ribonucleoprotein assembly. Little is known about Stau2 expression and function in mammalian oocytes during meiosis. Herein we report the sub-cellular distribution and function of Stau2 in mouse oocyte meiosis. Western blot analysis revealed high and stable expression of Stau2 in oocytes from germinal vesicle (GV) to metaphase II (MII). Immunofluorescence showed that Stau2 was evenly distributed in oocytes at GV stage, and assembled as filaments after germinal vesicle breakdown (GVBD), particularly, colocalized with spindle at MI and MII. Stau2 was disassembled when microtubules were disrupted with nocodazole, on the other hand, when MTs were stabilized with taxol, Stau2 was not colocalized with the stabilized microtubules, but aggregated around the chromosomes array, indicating Stau2 assembly and colocalization with microtubules require both microtubule integrity and its normal dynamics. During interphase and mitosis of BHK and MEF cells, Stau2 was not distributed on microtubules, but colocalized with cis -Golgi marker GM130, implying its association with Golgi complex but not the spindle in fully differentiated somatic cells. Specific morpholino oligo-mediated Stau2 knockdown disrupted spindle formation, chromosome alignment and microtubule-kinetochore attachment in oocytes. The majority oocytes were arrested at MI stage, with bright MAD1 at kinetochores, indicating activation of spindle assembly checkpoint (SAC). Some oocytes were stranded at telophase I (TI), implying suppressed first polar body extrution. Together these data demonstrate that Stau2 is required for spindle formation and timely meiotic progression in mouse oocytes.